CATECHONS IN SOCIO-ONOMASTIC DIMENSION - Honcharenko, D. (Linguistic and Conceptual Worldviews, 2020)
The article raises the question of necessity of normalization and standardization newly formed catechons in lexicographical aspect. A typical word- forming paradigm of catechons that appeared in Ukrainian onomasticon after 2015 is analysed. The attention is concentrated on word-forming ability of catechons and their lexical-semantic structure. The relevance of the study of catechonyms is indicated, first of all, by extra-lingual (socio-political and socio-cultural) factors. One of the impetus for the intensification of scientific research related to cateconomy was the Law of Ukraine «On Condemnation Communist and Nazi Totalitarian Regimes and Prohibiting the Propagation of Their Symbolism». The derivation process can be accompanied by morphonological processes: alternation, truncation, alternation with truncation. The typical word-forming paradigm of catechons has the following structure: the original forming basis (necessarily correlated with the catechon’s oikonym) - an appellative of masculine motivated by an oikononym (formed with the help of specific word-forming formants with the semantics «masculine- territorial personality»), an appellative of female corresponding to the appellative of the masculine gender, which in turn is defined by the forming noun (using word-forming formants with semantics, «female gender related to male territorial personality») - appellative in plural, also formed from the masculine appellative with the help of forming formants with the semantics» name of persons by territorial feature». The choice of the required catho- monetary suffix depends on such extralingual factors as the attraction to the euphony, the conscious return to the specific Ukrainian wording formulations, as well as intralingual - structural, semantic and functional specificity of the word-forming oiconym.